Antimicrobial resistance and genetic diversity of Salmonella enterica from eggs - Xie, Tengfei (Food Sci Nutr, 2019)
Salmonella enterica is a common foodborne pathogen responsible for major global health problems such as paratyphoid fever and gastroenteritis. Here, we report the prevalence, antibiotic resistance phenotypes, serotypes, and molecular subtyping of Salmonella isolated from eggs in Guangdong, China. Out of 1,000 egg samples, 54 (5.40%) were positive. S. Enteritidis made up the largest proportion of samples with 11 serotypes. Antimicrobial susceptibility test indicated that most strains were resistant to β‐lactam, aminoglycoside, and tetracycline antibiotics (27.00%–40.00%). There were 37 STs based on MLST typing. MLST and ERIC‐PCR classified 54 isolates into three and five clusters, respectively, which revealed the genetic relatedness and diversity. In conclusion, frequent monitoring of eggs for Salmonella, antibiotic resistance profiles and genetic diversity is essential for improving food safety.